Analisis Tindak Tutur Ilokusi pada Lagu Karya Denny Caknan dalam Minialbum Kalih Welasku (2023): Sebuah Kajian Pragmatik - Maulana, Adam; Mabruroh, Siti; Anwar, Alifia Nabila Putri; Lukman, Diva Sania; Ramadhanti, Annisa (J-LELC: Journal of Language Education, Linguistics, and Culture, 2026)
This study aimed to describe the productivity and functions of illocutionary speech acts in the mini album Kalih Welasku (2023) by Denny Caknan. Using a qualitative approach with descriptive analysis, the study sought to show how utterances in song lyrics built the speaker’s communicative intentions. The data were analyzed based on Searle’s theory of illocutionary speech acts, which classified illocution into five categories: assertive, directive, commissive, expressive, and declarative. This framework was applied to identify the types of utterances that appeared and to interpret the pragmatic functions underlying each line of the lyrics. The findings showed that four types of illocutionary speech acts appeared in the four songs included in the mini-album, namely assertive, directive, commissive, and expressive acts. Among all findings, assertive speech acts were the most dominant, indicating that the lyrics were largely used to state beliefs, describe conditions, or directly express the speaker’s thoughts. Directive, commissive, and expressive acts also appeared, but with lower frequency. Meanwhile, declarative speech acts were not found in the data, suggesting that the song lyrics did not contain utterances that changed social status or reality. These findings illustrated patterns of speech act usage in contemporary Javanese popular music.